2016
DOI: 10.1007/s00330-016-4695-6
|View full text |Cite
|
Sign up to set email alerts
|

Can lymphovascular invasion be predicted by preoperative multiphasic dynamic CT in patients with advanced gastric cancer?

Abstract: • Lymphovascular invasion rarely can be evaluated preoperatively in advanced gastric cancer (AGC). • Δ and Δ were independent predictors for LVI in patients with AGC. • Δ and Δ showed acceptable predictive performance for LVI. • Combination of Δ and Δ improved predictive performance for LVI. • Multiphasic dynamic CT may be a useful adjunct for detecting LVI preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…The current AJCC/UICC guidelines do not include LVI as an independent prognostic indicator of GC in the TNM staging system. However, many studies have shown that LVI is an independent risk factor for survival in GC patients [11,13,15,27,28]. Patients with LVI had been reported to be associated with poorer prognosis, and we also obtained similar results.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The current AJCC/UICC guidelines do not include LVI as an independent prognostic indicator of GC in the TNM staging system. However, many studies have shown that LVI is an independent risk factor for survival in GC patients [11,13,15,27,28]. Patients with LVI had been reported to be associated with poorer prognosis, and we also obtained similar results.…”
Section: Discussionsupporting
confidence: 83%
“…As a common preoperative examination, CECT was an effective tool for differential diagnosis, preoperative assessment, therapeutic and prognostic evaluation in patients with GC [3,13,18,21]. In this study, we built and validated radiomics models based on CECT for the noninvasive, preoperative individualized prediction of histological LVI status were associated with disease specific recurrence, suggesting that our findings can play an important role in the clinical treatment of GC.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Previous studies indicated that diffuse type (histopathological type according to Lauren classification) and Borrmann type IV (histopathological type according to Borrmann classification) patients were associated with poor prognosis (7,1214). Besides, several studies demonstrated that lymphatic vascular infiltration (LVI) of the tumor is an additional prognostic marker (6,7,15,16). Taken together, the histopathological status is an important risk factor and exerts excellent ability to classify survival of patients with GCs.…”
Section: Introductionmentioning
confidence: 99%